Social Constructivism-Based Reading Comprehension Teaching Design - Welly Ardiansyah; Murwani Ujihanti (LINGUA: Jurnal Bahasa dan Sastra, 2020)
Abstract: This study aimed to investigate students’ reading comprehension achievement, vocabulary mastery, and social values among students. The methodology was Research & Development (R&D). There were six classes involved in the research and grouped into three high classes and three low classes based on the reading comprehension and vocabulary placement test results. All classes were taught with the social constructivism-based reading comprehension teaching design in the phase of large fild testing in the academic year 2016/2017 with total number of 148 students; 72 in the high class and 76 the low students. To collect the data, tests of reading comprehension and vocabulary were used. Shapiro-Wilk test was used to the normality of data distribution. The fidings from the paired-sample t-tests showed signifiant diffrences revealing the effctiveness of the social constructivism-based reading comprehension teaching design. The article concludes with implications for pedagogy.Keywords: reading comprehension achievement, vocabulary mastery, social constructivismAbstrak: Penelitian ini bertujuan untuk mengetahui prestasi pemahaman membaca siswa, penguasaan kosakata, dan nilai-nilai sosial siswa. Metode yang digunakan adalah Research & Development (R&D). Terdapat enam kelas yang terlibat dalam penelitian ini dan dikelompokkan menjadi tiga kelas atas dan tiga kelas rendah berdasarkan hasil tes pemahaman membaca dan tes penempatan kosa kata. Semua kelas diajar dengan desain pembelajaran pemahaman membaca berbasis konstruktivisme sosial pada tahap uji coba lapangan besar pada tahun ajaran 2016/2017 dengan jumlah 148 siswa; 72 di kelas tinggi dan 76 di kelas rendah. Untuk mengumpulkan data digunakan tes pemahaman membaca dan kosakata. Uji Shapiro-Wilk digunakan untuk mengetahui normalitas sebaran data. Temuan dari uji-t berpasangan menunjukkan perbedaan yang signifian yang menunjukkan keefektifan desain pengajaran pemahaman membaca berbasis konstruktivisme sosial. Artikel ini memberikan kesimpulan dengan implikasi pedagogi.Kata-kata kunci: prestasi pemahaman membaca, penguasaan kosakata, konstruktivisme sosial